identifikasi betasianin dan uji antioksidan ekstrak kulit buah naga merah (Hylocereus polyrhiyus - Romdonah, Febri Siti; Kusumo, Ersanghono; Supartono, Supartono (Indonesian Journal of Chemical Science, 2017)
Red dragon fruit leather is the waste not utilized anymore, whereas dragon fruit contain pigmen betacyanin. The study aim to know pigmen betacyanin and antioxidant activity from the red dragon fruit leather extracts. The reasearch methode is extraction of dragon fruit leather with n-hexsane solvent and ethanol solvent. Identification of betacyanin and analyse antioxidant activity with HPLC and UV-Vis. The research obtained that betacyanin compound on the peak with retention time 2,77 and that was compared with the standard appears on retentiom time 2,85. Tested of antioxidant activity on vitamin C has a IC50 value is 2,54 Âµg/mL, whereas the IC50 value of extract dragon fruit is 59,12 Âµg/mL. Vitamin C have the antioxidant activity more powerful than red dragon fruit as the antioxidant activity. The calculation levels of betacyanin 36,67 mg/100g.